Video Mind Mapping Berbasis Etnosains Menggunakan Indigenous Knowledge Untuk Melatihkan Kemampuan Literasi Sains Siswa - Mochammad Yasir; Aushia Tanzih Al Haq Aushia; Parmin Parmin (JPPS (Jurnal Penelitian Pendidikan Sains), 2022)
Research aims to determine differences in scientific literacy skills and student responses after applying ethnoscience-based mind-mapping videos using indigenous knowledge. Type of research is pre-experimental with one group pretest-posttest design. The sample used was 22 students taken by purposive sampling technique. The data analysis technique used paired sample t-tests and descriptive statistics. Based on the study's results, it was found that (1) there were differences in students' scientific literacy skills before and after the application of ethnoscience-based mind mapping videos using indigenous knowledge, and (2) the average student response with very good criteria. The results of the application of ethnoscience-based mind mapping videos using indigenous knowledge have an impact on (1) science learning innovations in junior high schools and universities in teaching science material in the context of culture and local wisdom and developing scientific literacy skills of students and prospective science teacher students; and (2) strengthening the profile of Pancasila students using the promotion of diversity through ethnoscience. This research implies that how students practice their science literacy skills on indigenous knowledge can use video mind mapping in addition to e-modules, pop-up books/the like and help preserve local wisdom for the next generation.